2012
DOI: 10.1016/j.pec.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of race and socioeconomic status on engagement in pediatric primary care

Abstract: Objective To understand the association of race/ethnicity with engagement in pediatric primary care and examine how any racial/ethnic disparities are influenced by socioeconomic status. Methods Visit videos and parent surveys were obtained for 405 children who visited for respiratory infections. Family and physician engagement in key visit tasks (relationship building, information exchange, and decision making) were coded. Two parallel regression models adjusting for covariates and clustering by physician we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 60 publications
4
46
1
Order By: Relevance
“…An interaction effect between uncovered treatment costs and patients without residence permit shows an increase of SR and of CR. Taken as a whole, our results are in line with findings from earlier research indicating the importance of social categories for physicians' judgments (Cox et al, 2012;Moskowitz et al, 2012;Sabin et al, 2009;Sabin and Greenwald, 2012;Stepanikova, 2012). In our study patients' characteristics such as origin, residence, or economic status alter the willingness to treat patients immediately, independent of medical urgency, physicians' time pressure, or the question of covered treatment costs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An interaction effect between uncovered treatment costs and patients without residence permit shows an increase of SR and of CR. Taken as a whole, our results are in line with findings from earlier research indicating the importance of social categories for physicians' judgments (Cox et al, 2012;Moskowitz et al, 2012;Sabin et al, 2009;Sabin and Greenwald, 2012;Stepanikova, 2012). In our study patients' characteristics such as origin, residence, or economic status alter the willingness to treat patients immediately, independent of medical urgency, physicians' time pressure, or the question of covered treatment costs.…”
Section: Discussionsupporting
confidence: 91%
“…Even though we have not found a significant interaction effect between ethnicity or the residence status, the single effect of this factor highlights the multifactorial sources of ethnic disparities in health care. Other studies indicate that ethnical disparities are influenced by socioeconomic status (Cox et al, 2012). Even if medical education aims at training health professionals for the treatment of migrant patients, effective teaching methods should therefore also focus beyond ethnicity and involve the discussion of other factors, e.g.…”
Section: Respondent Characteristicsmentioning
confidence: 99%
“…28 ) that correlate with patient race could account for some or most of the differential prescribing rates apparent in these analyses, consistent with previous reports. 9,29 Practitioner bias affecting medical decision-making by patient race and socioeconomic status has been described, 1,30 but its relevance to the diagnosis and treatment of ARTIs is unclear. Because overprescribing of antibiotics to children with ARTIs is common, [5][6][7] we hypothesize that this discrepancy reflects overprescribing, both for all antibiotics and for the relative proportion of broad-spectrum antibiotics, to nonblack patients, rather than underprescribing to black patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was often reported that patients with different ethnic backgrounds did not know how to enter the healthcare system, how to make an appointment with the doctor or which person with a high social status and regarded it as disrespectful to contradict the doctor (paternalism). [43,72,79,88,90,97,[122][123][124]127,[130][131][132][133][134][135][136][137][138][139][140] In these cases, patient-centered communication might be a effective approach for ICC.…”
Section: Differences In Cultural Perception Of Illness and Diseasementioning
confidence: 99%
“…[54,73,76,[78][79][80]83,84,87,105,114,152] Also, time management [54,76,[79][80][81][82][83]87,89,105,107,108,152], providing explanations [34,73,76,80,85,100,102,107,108,119,149,152] and giving appropriate information [63,69,84,87,110,114,121,127,131,132,147,[153][154][155] were mentioned as core skills for a doctor to facilitate ICC communication.…”
Section: Differences In Cultural Perception Of Illness and Diseasementioning
confidence: 99%